Archaeology of Southern Urban Landscapes - Young, Amy L. (Book collections on Project MUSE., 2009)
The rapid growth and development of urban areas in the South have resulted in an increase in the number of urban archaeology projects required by federal and state agencies. These projects provide opportunities not only to investigate marginal areas between the town and countryside but also to recover information long buried beneath the earliest urban structures. Such projects have also created a need for a one-volume update on archaeology as it is practiced in the urban areas of the southeastern United States. Archaeology of Southern Urban Landscapes will assist practi.